Recurrent drop attacks in early childhood as presenting symptom of benign hereditary chorea caused by TITF1 gene mutations. (20th November 2014) - Rosati, Anna; Berti, Beatrice; Melani, Federico; Cellini, Elena; Procopio, Elena; Guerrini, Renzo
<x xml:space="preserve">Abstract</x> Drop attacks are sudden, spontaneous falls without loss of consciousness, followed by rapid recovery. Causes in children include severe epilepsies, movement disorders, cataplexy, and psychiatric disorders. We describe two children (a 3‐year‐old female and a 12‐year‐old male) with mild neuromotor delay and sudden falls appearing upon starting to walk. Extensive clinical and laboratory investigation was unremarkable. Twenty to 22 months after the onset of falls, both children developed subtle choreiform movements, affecting all four limbs, leading to frequent falls, at times causing traumatic injury. A heterozygous mutation of the TITF1/NKX2‐1 gene (14q13) was detected in both patients, allowing the diagnosis of benign hereditary chorea (BHC). Treatment with levodopa attenuated abnormal movements and led to disappearance of drop attacks. A diagnosis of BHC should be considered in young children with recurrent and unexplained drop attacks, especially if associated with neuromotor delay, even in the absence of choreiform movements.